Effects of downscaling channel dimensions on electrical characteristics of InAs-FinFET transistor - Ahmed Mahmood; Waheb A. Jabbar; Yasir Hashim; Hadi Bin Manap (Institute of Advanced Engineering and Science, 2019)
In this paper, we present the impact of downscaling of nano-channel dimensions of Indium Arsenide Fin Feld Effect Transistor (InAs- FinFET) on electrical characteristics of the transistor, in particular; (i) ION/IOFF ratio, (ii) Subthreshold Swing (SS), Threshold voltage (VT), and Drain-induced barrier lowering (DIBL). MuGFET simulation tool was utilized to simulate and compare the considered characteristics based on variable channel dimensions: length, width and oxide thickness. The results demonstrate that the best performance of InAs- FinFET was achieved with channel length = 25 nm, width= 5 nm, and oxide thickness between 1.5 to 2.5 nm according to the selected scaling factor (K = 0.125).